Semantic and pragmatic motivations on grammatical change - Sousa, Gisele Cassia de [UNESP] (Univ Fed Minas Gerais, Dept Filosofia & Ciencias Humanas, 2015)
This paper aims to demonstrate the influence of semantic and pragmatic factors on linguistic change processes. The study focuses on complement clauses in the Portuguese language, particularly the one introduced by the conjunction se (if/whether), which is the homonym of the conjunction that introduces the conditional clause. By tracking the origin of this complement clause in Portuguese, the research seeks to explain the reasons for formal identity between the two conjunctions se observed not only in Portuguese, but also in most Romance languages. Based on statements of philologists and Romanists, this study reveals that the similarity between conjunctions is explained by the etymology of the complementizer se, arising from the Latin conjunction si that replaced the interrogative particles in Latin. As it is argued in the text, this replacement would have been made possible by semantic and pragmatic properties shared by interrogative and conditional clauses. Therefore, these meanings and common features between the two clauses show that the homonym between forms of conditionals and indirect questions in Romance languages is not fortuitous. The origin of a conditional clause, whose meaning is basically a hypothesis, also explains why the completive clause introduced by se in Portuguese is not grammaticalized in the same way as a completive clause introduced by que (that). More broadly, the analyses demonstrate that semantic and pragmatic factors can determine a specific trajectory of change to a linguistic form. In conclusion, this study emphasizes the importance of considering semantic and pragmatic aspects, parallel to formal aspects, in researches on language change.
Keywords: grammatical change; semantic and pragmatic motivations; complement clauses; grammaticalization